What are the economic and poverty implications for Sudan if the conflict continues through 2024? - Ahmed, Mosab O. M.; Raouf, Mariam; Siddig, Khalid (International Food Policy Research Institute, 2024)
The conflict in Sudan, which started in April 2023, has led to severe economic repercussions, sharply reducing the country's Gross Domestic Product (GDP), employment, and household incomes and increasing the prevalence of poverty. Using an updated economywide database for Sudan, we ran an analysis of the likely economic impact of a continuation of the conflict through to the end of 2024 using two scenarios of extreme and moderate reductions in overall GDP. These reductions are triggered mainly by the ongoing conflict, which is causing additional cuts in the operations of business services and continuing disruptions to wholesale and retail services and manufacturing. The results of the analysis show a 47 percent decline in Sudan’s GDP under the extreme reduction scenario and a 13 percent decline under the moderate scenario relative to 2022 before the conflict began. Under the extreme scenario, the agrifood system GDP falls by 26 percent and employment by 50 percent, with non-farm jobs being more adversely affected. Household incomes decline significantly across all quintiles and in both rural and urban areas, with urban and richer households facing slightly higher reductions. Less-educated labor categories are severely affected, while tertiary-educated labor shows relative resilience. Poverty rates have surged, particularly in rural areas and among women, with the national poverty rate estimated to have increased by 21 percentage points under the extreme reduction scenario. To mitigate the widespread adverse impacts of the conflict on the Sudanese economy and foster long-term resilience, policies and interventions should prioritize the restoration of economic productivity, provide support for the agrifood system and employment recovery strategies, and ensure that social protection measures are accessible to all households facing increased deprivation.